Pedagogical and Psychological Aspects of the Landscape Genre in Art Education - Tursunova Dilshoda Jahongirovna (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
ANNOTATION: This article examines the pedagogical and psychological aspects of teaching the landscape genre in art education. It explores strategies for enhancing students’ artistic skills, creative thinking, and emotional engagement through landscape drawing. The study emphasizes the importance of understanding both educational and psychological factors in lesson planning, including motivation, perception, attention, and cognitive development. By integrating pedagogical principles with psychological insights, teachers can create effective learning experiences that foster compositional skills, spatial awareness, and aesthetic appreciation in students.